Implementation of Wordwall-Based Interactive Games on Early Reading Skills: A Case Study at SDN Talabiu Bima - Fibriana, Fira; Irawati, Ika; Haryadi, Didit (FKIP - Universitas Riau, 2025)
The objectives of this study are: (1) To evaluate the extent of the effectiveness of Wordwall games on improving students' beginning reading skills (2) to examine the effect of using Wordwall-based interactive games on students' beginning reading skills. This study used a quantitative approach with a quasi-experimental method and a one group pretest-posttest design. this research was conducted in class II of SDN Talabiu. Data collection techniques used in this study include questionnaires that have proven their validity and reliability through the use of data analysis methods such as normality tests, descriptive tests and Paired Sample T-Test tests conducted using the SPSS 25 program. The results showed that there was an increase in scores from 53.32 in the pretest to 79.52 in the posttest significance level of 0.000 which indicates that the use of wordwall games has a significant effect on improving students' beginning reading skills. Thus, this study proves that the use of Wordwall interactive game media is effective and has a significant effect on students' beginning reading skills.